Hemorrhagic Descemet Membrane Detachment Following Syphilitic Interstitial Keratitis. Issue 9 (September 2016) - Höllhumer, Roland; Zairani MZ, Aida; Watson, Stephanie
Abstract : Purpose: Syphilitic interstitial keratitis is a stromal inflammatory disease with characteristic secondary vascularization. This case illustrates a late complication of hemorrhagic Descemet membrane detachment. Methods: Case report. Results: The patient presented with painless sudden visual loss and progressive shallowing of the anterior chamber caused by hemorrhagic Descemet membrane detachment. She had corneal neovascularization and a positive syphilis serology. Owing to the risk of pupil block glaucoma, the patient had surgical drainage of the blood via an ab externo approach. Conclusions: This case illustrates a previously unreported complication of syphilitic interstitial keratitis. The patient recovered good visual acuity and had residual pigment deposits in the pre-Descemet interface.